DURATION OF CYSTIC DUCT DISSECTION AS AN INDICATOR OF CHALLENGING LAPAROSCOPIC CHOLECYSTECTOMY. - Prakash, Ved; Abhishek, Kumar; Sangwan, Pratik (Student's Journal of Health Research Africa, 2023)
Background: The Tokyo 2018 guidelines recommend investigating quantitative predictors of surgical complexity in laparoscopic cholecystectomy to ensure safe and effective gallbladder removal. Objective: This study aims to evaluate the duration of cystic duct (CD) dissection as a potential indicator of surgical complexity. Materials and Methods: A prospective study with 190 individuals scheduled for laparoscopic cholecystectomy was carried out. Depending on the reason for the cholecystectomy, people were divided into three categories: elective, delayed, and urgent. The study utilized both multinomial logistic regression and multiple linear regression analysis to determine the preoperative and operative predictive variables associated with surgical difficulties. Results: The duration of CD dissection was observed to be 12 minutes, exhibiting a sensitivity of 100% and specificity of 99%. The positive predictive value (PPV) was determined to be 100%, while the negative predictive value (NPV) was found to be 1%. The odds ratio (OR) was calculated to be 2.3, indicating a predictive capacity for the utilization of bailout techniques. Conclusion: The duration of cystic duct dissection, regardless of its outcome, serves as a practical indicator for the likelihood of employing bailout procedures and thus predicts the probability of encountering a "Risk/Difficult Cholecystectomy".